Iron oxide nano-fertiliser enhancing chilli growth / Nurul Izza Taib ... [et al.] - Taib, Nurul Izza; Hashim, Saiyidah Nafisah; Adam, Nurul Ilham; Abdul Aziz, Rosmawati (2024)
Iron oxide nanoparticles (Fe3O4-NPs) were synthesised using a mixture of rabbit urine and golden apple snails, using a greener approach. TEM analysis shows that the green synthesis Fe3O4-NPs were well agglomerated; the average particle size of Fe3O4-NPs was found to be 12 nm. The aim of this study is to assess their use as potential nanourine (NU) fertilisers for chilli plants' growth. There are five treatments: negative control, Fe3O4-NPs alone without urine (80%), Fe3O4-NPs combination with urine (25% NU, 50% NU, and 100% NU) were experimented on the grouped plants. It was found that 25% NU treatment is the optimum concentration to enhance chilli plant growth, giving the highest growth rate in plant leaves and stems. This formulated nano-urine fertiliser from rabbit urine might contain components that play a crucial role in promoting plant growth as it may be included with important nutrients, such as nitrogen, phosphate and potassium. The nanosize of this NU observed might cause better penetration into plant cells, ensuring efficient utilisation of the nutrients. This leads to improved crop yields and overall plant health, making it an eco-friendly and sustainable solution for agriculture.